VISUALIZATION OFMATH FORMULASWAKE UP AND EXERCISE ROOM AND INTERACTIVE PROBLEM USING MICROSOFT VISUAL BASIC 6.0 - PRINCESS Soraya (Jurnal Manajemen Informatika, 2010)
In the current era of globalization, the development of science, technology and information increasinglyfast and sophisticated. Many all fields associated with the computer because with a computer variouskinds of knowledge can be searched here. With easy to obtain such knowledge, the authors areinterested in creating applications with a collection of mathematical formulas using Ms Visual Basic 6.0.Application is made to meet the needs of the learning process for students because the authors saw thestudents are still very difficult to learn the formula to memorize formulas built let alone get up inaddition to that they were also hit by the existing curriculum so that did not have time to explore andunderstand more about the formula wake mathematics, using electronic media is the author hopes theycan better understand the mathematical formulas built and no longer considered a scourge that must befeared.